2011
DOI: 10.1029/2011jd015753
|View full text |Cite
|
Sign up to set email alerts
|

Variation of accumulation rates over the last eight centuries on the East Antarctic Plateau derived from volcanic signals in ice cores

Abstract: [1] Volcanic signatures in ice-core records provide an excellent means to date the cores and obtain information about accumulation rates. From several ice cores it is thus possible to extract a spatio-temporal accumulation pattern. We show records of electrical conductivity and sulfur from 13 firn cores from the Norwegian-USA scientific traverse during the International Polar Year 2007-2009 (IPY) through East Antarctica. Major volcanic eruptions are identified and used to assess century-scale accumulation chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 47 publications
7
54
0
Order By: Relevance
“…This is parallel to an increase in temperature (derived from stable isotopes) and thus most likely caused thermodynamically (Altnau et al, 2015). Anschütz et al (2009Anschütz et al ( , 2011 found no clear overall trend in SMB based on data from a traverse from coastal DML to the South Pole, with an increase at some sites and a decrease at others. However, above 3200 m, all sites exhibited a decrease in SMB since 1963. report that SMB data from a traverse between Dome Fuji and EPICA DML is strongly influenced by topography and is found to be approximately 15 % higher in the second half of the 20th century than averages over centennial or millennial averages.…”
Section: Drivers Of Regional Precipitation 321 East Antarctic Platementioning
confidence: 95%
“…This is parallel to an increase in temperature (derived from stable isotopes) and thus most likely caused thermodynamically (Altnau et al, 2015). Anschütz et al (2009Anschütz et al ( , 2011 found no clear overall trend in SMB based on data from a traverse from coastal DML to the South Pole, with an increase at some sites and a decrease at others. However, above 3200 m, all sites exhibited a decrease in SMB since 1963. report that SMB data from a traverse between Dome Fuji and EPICA DML is strongly influenced by topography and is found to be approximately 15 % higher in the second half of the 20th century than averages over centennial or millennial averages.…”
Section: Drivers Of Regional Precipitation 321 East Antarctic Platementioning
confidence: 95%
“…An example of such efforts is the Norwegian-USA traverse (IPY) through East Antarctica. The traverse has provided new data sets for the SMB based on ground-based accumulation measurements through large parts of DML to the South Pole (Anschütz et al, 2009(Anschütz et al, , 2011Müller et al, 2010).…”
Section: Surface Mass Balance Of Antarcticamentioning
confidence: 99%
“…In addition, Isaksson et al (1999) found that a general increase in accumulation rate, particularly in the latter part of the 20th century, was not necessarily the case for the whole polar plateau of DML. More recently, Anschütz et al (2011) presented results from the Norwegian-USA scientific traverse. They reported that the largest changes seem to have occurred in the most recent decades with accumulation rates over the period 1963-2007/08 being up to 25 % different from the long-term record.…”
Section: Earlier Studies Of Regional Smbmentioning
confidence: 99%
See 2 more Smart Citations